Pengaruh Word Of Mouth, Citra Merek dan Daya Tarik Iklan terhadap Keputusan Pembelian Smartphone Iphone di Kabupaten Badung - Kadek Agus Adi Gunawan; Ni Made Rastini (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Competition in the smartphone industry in Indonesia is getting tighter due to the high demand of the public for smartphones to support their daily activities. The purpose of this study is to explain the influence of word of mouth, brand image and advertising on the decision to purchase iPhone smartphones in Badung Regency. The method of determining the sample of this study uses non-probability sampling with purposive sampling technique with a sample of 140 people. The analysis techniques used are multiple linear analysis, F test, t test, and determination test. The results of the study indicate that word of mouth has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, advertising has a positive and significant effect on purchasing decisions, word of mouth, brand image, and advertising have a simultaneous or simultaneous effect on purchasing decisions, and brand image has a dominant effect on purchasing decisions. The practical implications of this study are that it can be a consideration for iPhone brand management to improve marketing strategies and product development of the iPhone brand, thereby further strengthening the brand's position in the market and increasing consumer purchasing decisions. The method of determining the sample for this study uses non-probability sampling with a purposive sampling technique, selecting a sample of 140 people who are familiar with the iPhone brand. The analysis techniques used include multiple linear regression analysis, F test, t test, and the determination test. These techniques help to determine the individual and combined effects of word of mouth, brand image, and advertising on purchasing decisions. The results of the study indicate that all three factors—word of mouth, brand image, and advertising—have a positive and significant effect on purchasing decisions.